IMPROVING THE TECHNOLOGY OF REFINING LOCAL RAW SOYBEAN OILS UNDER THE INFLUENCE OF AN ELECTROMAGNETIC FIELD - K. B. Yorov; S. Sh. Ismatov; K. Kh. Majidov (Journals Park Publishing, 2025)
Methods of using the influence of an electromagnetic field in the refining process of vegetable oils obtained from local soybean seeds were studied. As a result of applying electromagnetic effects of various intensities, it was achieved to increase the quality indicators of refined soybean oils, as well as to improve their physicochemical characteristics.
Keywords: Local oily soybean seeds, vegetable oils, alkaline refining processes, oil quality indicators, physicochemical characteristics.